(untitled) (Gaceta de Ciencias Veterinarias, 2018)
The objective of this research is to determine the effect of melatonin on superoxide dismutase (SOD) in seminal plasma and sperm membrane integrity during storage at 16°C. Methodology: Boar seminal samples were taken between 7-18 months of age using manual technique of gloved hand extraction in Inversiones Porcinas C.A. The optimal samples were diluted and aliquoted: control (with diluent), vehicle control (diluent and ethanol), semen with melatonin (1.25 mM), aliquots being stored at 16ºC for subsequent evaluation at day 0 and 1 of the preparation. The enzymatic activity of SOD (commercial kit Cayman®) and membrane integrity (hypo-osmotic test) was evaluated. The results were analyzed by means of ANOVA, with statistical package SPSS 15.0 for Windows with p<0.05. Results: the samples with melatonin on day 0 presented greater enzymatic activity without significant differences, sustained until day 01 with significance (p<0.05) in comparison to the control group; with respect to membrane integrity (HOST +) the samples with melatonin presented a significant elevation (p<0.05) of the percentage of HOST + sperm in difference to other groups at day 0 of preservation, keeping on day 01 of conservation. Conclusion: Melatonin improves the activity of SOD in seminal plasma and membrane integrity during the conservation of pig semen at 16 °C.